CAR-HEMATOTOX score as a predictor of hematotoxicity, infection, and survival after CAR T-cell therapy in hematologic malignancies: a systematic review and meta-analysis - Juncheng Wei; Ziyu Chen; Mengfei Li; Miao Jiang (Frontiers in Oncology, 2026)
Background Immune effector cell-associated hematotoxicity (ICAHT) is a common and clinically important toxicity after chimeric antigen receptor (CAR) T-cell therapy. The CAR-HEMATOTOX score, also reported as CAR-HT, is a baseline risk score proposed to identify patients at higher risk of hematotoxicity and related adverse outcomes. Methods We conducted a systematic search of PubMed, the Web of Science, and the Cochrane Library on June 19, 2026. Included studies compared high- and low-risk groups defined by the CAR-HEMATOTOX score after CAR T-cell therapy for hematologic malignancies and reported extractable data on hematologic toxicity, infection, survival, or other predefined clinical outcomes. Random-effects inverse-variance meta-analysis was performed only when at least three independent, clinically compatible estimates were available. Results Twenty-three publications were included in the evidence inventory. For ICAHT, high risk was associated with higher odds (pooled OR 5.58, 95% CI 1.98 to 15.73; I²=60.8%). For overall survival (OS), high risk was associated with worse OS (pooled HR 3.36, 95% CI 2.20 to 5.11; I²=0.0%). For progression-free survival (PFS), high risk was associated with worse PFS (pooled HR 2.74, 95% CI 1.81 to 4.15; I²=32.3%). For severe infection, high-risk status was associated with higher odds (pooled OR 5.18, 95% CI 2.78 to 9.67; I²=37.8%). Exploratory analyses suggested higher early red blood cell and platelet transfusion requirements in high-risk patients, whereas severe cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS) were not significantly associated with high-risk status. Conclusion A high CAR-HEMATOTOX score was associated with greater risk of ICAHT, higher odds of severe infection, and worse survival outcomes after CAR T-cell therapy for hematologic malignancies. These findings suggest that the CAR-HEMATOTOX score may be a clinically relevant risk-stratification marker, but the evidence remains observational and exploratory; standardized outcome definitions, prospective validation, and clearer handling of overlapping cohorts are needed before the score can be used as a stand-alone decision tool. Systematic Review Registration https://www.crd.york.ac.uk/prospero/view/CRD420261435303 , identifier 420261435303.